Perspective: Something Old, Something New? Review of Wasting and Other Mortality in Asteroidea (Echinodermata) - Hewson, Ian; Sullivan, Brooke; Jackson, Elliot W.; Xu, Qiang; Long, Hao; Lin, Chenggang; Quijano Cardé, Eva Marie; Seymour, Justin; Siboni, Nachshon; Jones, Matthew R. L.; Sewell, Mary A. (Frontiers in Marine Science, 2019)
Asteroids (Echinodermata) experience mass mortality events that have the potential to cause dramatic shifts in ecosystem structure. Asteroid wasting describes a suite of body wall abnormalities that can ultimately result in animal mortality. Wasting in Northeast Pacific asteroids has gained considerable recent scientific attention due to its geographic extent, number of species affected, and effects on overall population density in some affected regions. However, asteroid wasting has been observed for over a century in other regions and species. Asteroids are subject to physical injury and adverse environmental conditions, which may result in very similar external manifestations to wasting, making identification of causative processes sometimes problematic. Here we review asteroid health abnormalities reported in years prior to the 2013–present Northeast Pacific wasting mass mortality, and report two additional geographically disparate wasting events that occurred concomitantly with the recent wasting outbreak.